The clinical role of VeriStrat testing in patients with advanced non–small cell lung cancer considered unfit for first-line platinum-based chemotherapy. (October 2019) - Lee, Siow Ming; Upadhyay, Sunil; Lewanski, Conrad; Falk, Stephen; Skailes, Geraldine; Woll, Penella J.; Hatton, Matthew; Lal, Rohit; Jones, Richard; Toy, Elizabeth; Rudd, Robin; Ngai, Yenting; et al.
Abstract: Purpose: We previously demonstrated that the median survival of patients with poor prognosis non–small cell lung cancer (NSCLC) considered unfit for first-line platinum chemotherapy was <4 months. We evaluated whether VeriStrat could be used as a prognostic or predictive biomarker in this population. Experimental design: We conducted a randomised double-blind trial among patients with untreated advanced NSCLC considered unfit for platinum chemotherapy because of poor performance status (PS) or multiple comorbidities. All patients received active supportive care (ASC) and were treated with either oral erlotinib or placebo daily. Five hundred twenty-seven patients had plasma samples for VeriStrat classification: good (VeriStrat Good [VSG]) or poor (VeriStrat Poor [VSP]). Main end-point was overall survival. Results: Fifty-five percent patients had VSG, and 83% had Eastern Cooperative Oncology Group (ECOG) 2–3 at baseline. VeriStrat was strongly associated with survival. Among patients managed with ASC only, the adjusted hazard ratio (HR) was 0.54 (p < 0.001) for VSG versus VSP. The association was consistent across patient factors: HR = 0.25 (p = 0.004) and HR = 0.56 (p < 0.001) for ECOG 0–1 and 2–3, respectively, HR = 0.49 (0070 < 0.001) for age≥75 years and HR = 0.59 (p = 0.007) for stage IV. Several ECOG 2–3 patients had long survival: 2-year survival was 8% for VSG patients who had ASC, compared with 0% for VSP. VeriStrat status did not predict benefit from erlotinib treatment because the HRs for erlotinib versus placebo were similar between VSG and VSP patients. Conclusions: VeriStrat was not a predictive marker for survival when considering first-line erlotinib for patients with NSCLC who had poor PS and were not recommended for platinum doublet therapies. However, VeriStrat was an independent prognostic marker of survival. It represents an objective measurement that could be considered alongside other patient factors to provide a more refined assessment of prognosis for this particular patient group. VSG patients could be selected for treatment trials because of better survival, while VSP patients can continue to be treated conservatively or offered trials of less toxic agents. Trial registration ISRCTN Number: ISRCTN02370070. Highlights: 83% advanced NSCLC patients unfit for chemotherapy have poor performance status. VeriStrat (proteomic blood test) is an independent prognostic marker for survival. Patients classified as VeriStrat Good were less likely to die than those classified as VeriStrat Poor. VeriStrat can refine patient prognosis in order to alter treatment management.